OXIDATIVE STRESS AND THYMUS MORPHOLOGY IN COLON CARCINOGENESIS UNDER THE INFLUENCE OF AU/AG/FE NANOCOMPOSITE - Kramar, S.B.; Andriichuk, I.Ya.; Lytvynyuk, S.O.; Soroka, S.Yu.; Nebesna, Z.M. (World of Medicine and Biology, 2025)
The purpose of the study was to determine the effect of the Au/Ag/Fe nanocomposite on oxidative stress indicators and the histological state of the thymus under conditions of induced carcinogenesis.N, N-dimethylhydrazine-induced carcinogenesis triggers pronounced oxidative stress in the thymus, demonstrated by significant increases in lipid and protein peroxidation markers: diene and triene conjugates and thiobarbituric acid reactive substances rose 1.30-, 1.22-, and 2.79-fold, respectively, while Schiff bases increased 2.01-fold. This oxidative damage is accompanied by suppression of the thymic antioxidant system, with reductions in superoxide dismutase, catalase, reduced glutathione, glutathione peroxidase, and glutathione reductase activities, indicating impaired redox homeostasis. Administration of an Au/Ag/Fe nanocomposite during carcinogenesis partially attenuated oxidative stress, led to restored antioxidant enzyme activities, and increasing of thymocyte density by 1.16-fold, suggesting both antioxidant and immunoprotective effects. These findings support further investigation of nanocomposites in mitigating thymic dysfunction under neoplastic conditions.
Keywords: oxidative stress; Au/Ag/Fe nanoparticles; thymus; N; N-dimethylhydrazine dihydrochloride; induced colon carcinogenesis